Pengaruh Media Baamboozle terhadap Hasil Belajar SKI Materi Hijrah Nabi di MI Madinatul Ulum Tembelang Jombang - Fikroh, Faza Mufidatul; Ashoumi, Hilyah (Lembaga Yasin AlSys, 2025)
This study aims to determine the effect of the media Baamboozle on the learning outcomes of Islamic History (SKI) students in Phase B regarding the material